2016
DOI: 10.1074/jbc.m116.730069
|View full text |Cite
|
Sign up to set email alerts
|

The Structurally Plastic CH2 Domain Is Linked to Distinct Functions of Fimbrins/Plastins

Abstract: Fimbrins/plastins have been implicated in the generation of distinct actin structures, which are linked to different cellular processes. Historically, fimbrins/plastins were mainly considered as generating tight actin bundles. Here, we demonstrate that different members of the fimbrin/plastin family have diverged biochemically during evolution to generate either tight actin bundles or loose networks with distinct biochemical and biophysical properties. Using the phylogenetically and functionally distinct Arabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…We therefore investigated tip-directed vesicle transport in Arabidopsis strains with altered filament binding status due to mutations in genes encoding actin-binding proteins. Indeed, we found that fim5 mutant pollen tubes, which have disorganized apical actin filaments (Supplemental Figure 4A; Zhang et al, 2016aZhang et al, , 2016b, exhibited defects in apical vesicle accumulation (Supplemental Figure 4B and 4C). To determine whether cortical or internal or both types of apical actin filament are vital for tip-directed vesicle transport, we performed FRAP in pollen tubes expressing Lat52::YFP-RabA4b.…”
Section: Apical Actin Filaments At the Cortex Drive Tip-directed Vesimentioning
confidence: 91%
See 1 more Smart Citation
“…We therefore investigated tip-directed vesicle transport in Arabidopsis strains with altered filament binding status due to mutations in genes encoding actin-binding proteins. Indeed, we found that fim5 mutant pollen tubes, which have disorganized apical actin filaments (Supplemental Figure 4A; Zhang et al, 2016aZhang et al, , 2016b, exhibited defects in apical vesicle accumulation (Supplemental Figure 4B and 4C). To determine whether cortical or internal or both types of apical actin filament are vital for tip-directed vesicle transport, we performed FRAP in pollen tubes expressing Lat52::YFP-RabA4b.…”
Section: Apical Actin Filaments At the Cortex Drive Tip-directed Vesimentioning
confidence: 91%
“…To visualize the arrangement and dynamics of actin filaments in tobacco and lily pollen tubes, microparticle bombardment was employed according to previously published papers (Twell et al, 1989;Zhang et al, 2016b). The expression of Lifeact-eGFP in tobacco and lily pollen tubes was under the control of the promoters of Lat52 and Zm13, respectively (Hamilton et al, 1992).…”
Section: Transient Gene Expression In Tobacco and Lily Pollen Tubesmentioning
confidence: 99%
“…Each L-plastin monomer can bind two adjacent molecules of filamentous actin, stabilizing the parallel strands. Illustration by ZJC; L-plastin structure based on [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary for pollen germination and pollen tube growth. [36][37][38] Except AtFIM5, chip data showed that AtFIM4 was also expressed in pollen tubes. Biochemistry data showed AtFIM4 made microfilaments bundle and branch, while AtFIM5 could only make microfilament bundle.…”
mentioning
confidence: 99%
“…Biochemistry data showed AtFIM4 made microfilaments bundle and branch, while AtFIM5 could only make microfilament bundle. 38 In vivo, AtFIM4 acts coordinately with AtFIM5 to organize and maintain the longitudinal actin bundles in pollen tubes. 39 In this study, the wild type (WT) and mutant seeds (atfim4-1/atfim5-2) were spread on 1/2MS medium with 250 nM indole-3-acetic acid (IAA), and after seven days germination, the root hair length was measured.…”
mentioning
confidence: 99%